Study on effect of different reservoir water diversion modes on river water quality improvement. Issue 1 (July 2021) - Dong, F; Huang, A; Peng, W; Liu, X
Abstract: Urban river water pollution is a serious environmental issue and tends to become worse. One of the key measures to improve urban river water quality is to divert water from upstream reservoir to downstream river course to flush pollutant. In this paper, a one-dimensional hydrodynamic and water quality model of Hun River network was developed based on HEC-RAS model. Different reservoir water diversion modes for sewage discharge were simulated and their effect on the water quality improvement of downstream river course was analysed. The results show that under different diversion flow rates, the larger the diversion flow rate, the better the effect on water quality improvement, and that when total water diversion volume is fixed, the effect of long-term diversion with a low flow rate is better than that of short-term diversion with a high flow rate on downstream water quality improvement. The research results can provide scientific support for optimization of the operation of water diversion from reservoir for sewage discharge.